Effect of online courses on US college students’ knowledge about health disparities - Njoku, Anuli (Health Education Journal, 2019)
Objective: To describe faculty efforts to deliver and evaluate health disparities–related education in US online undergraduate and graduate public health courses. Design: A pre- and post-survey was given to a cohort of 46 US college students in three public health courses taught asynchronously online over an 8-week period in 2017. This study took place at a mid-sized, public, rural, midwestern US university. Method: Faculty received professional development and online training and were assigned to develop courses for a new public health programme. Following the receipt of ethical approval, students completed anonymous, online pre- and post-surveys to assess effect of intentional instructional approaches on their knowledge and attitudes about health disparities. Curricula incorporated various assessment methods and teaching strategies. Descriptive statistics were used to compare pre- and post-survey scores and analyse demographic data. Paired t-tests and one-way analysis of variance were used to analyse pre- and post-survey test scores. Results: At post-survey, students demonstrated a positive change in mean scores for several items, including for ability to discuss the role of theory in understanding health behaviour and disparities in health status (3.20 vs 4.06; p < .001) and ability to discuss strategies health promotion programmes can use to reduce health disparities (3.47 vs 4.40; p < .001). Post-survey response rate was 87%. Conclusion: Results suggest an effective way to increase health disparities knowledge among online college students. Additional research is encouraged to expand upon these findings.
Keywords: dept.pch; peer-reviewed

Infusing Health Disparities Awareness Into Public Health Curricula at a Rural Midwestern University - Njoku, Anuli; Wakeel, Fathima (Pedagogy in Health Promotion, 2019)
Preventable differences in health outcomes between U.S. population subgroups, related to factors such as race or ethnicity, income, and geographic location, are troubling. Geographically, rural American communities experience higher rates of adverse health conditions when compared with urban areas, further widening disparities in health outcomes. Such disparities necessitate the creation of effective curricula to enable students to address the health needs of underserved populations. By intentionally incorporating health disparities awareness content into the curricula, undergraduate and graduate public health programs can play an integral role in developing conscious health practitioners to help close gaps in health outcomes. Moreover, rural health courses may increase students’ interest in rural health careers. This article presents the process and results of faculty efforts to design and deliver health disparities–related education in undergraduate and graduate public health courses at a rural Midwestern U.S. university. Various teaching development programs inspired faculty to use intentional instructional approaches to teach students about health disparities. Consequently, faculty incorporated a variety of assessment methods and teaching styles to infuse health disparities awareness content into public health courses. Results from students’ course evaluations and reflections are discussed along with lessons learned and implications for future pedagogical directions.
Keywords: dept.pch; peer-reviewed